Efficiency Study of Fluidized Aerobic Bioreactor Technology in Sewage Treatment Plant of Industrial Complex at Barbil, India - Dash, A.K.; Sahu, S.K.; Pradhan, A.; Dash, S.K.; Kolli, R.N. (Asian Journal of Chemistry, 2016)
Efficiency of sewage treatment plant employing fluidized aerobic bioreactor technology in an industrial complex at Barbil, Odisha, India was studied. Parameters like pH, TSS, BOD, COD, oil and grease were monitored. There is a considerable reduction of parameters in outlet samples with respect to inlet samples (81.5 % TSS, 94.65 % BOD, 85.51 % COD, 91.66 % oil and grease). pH changes from neutral to slightly alkaline. One way ANOVA test shows the significance reduction of different parameters (F = 14.13 for pH, F = 831.3 for TSS, F = 7759.8 for BOD, F = 9276.72 for COD and F = 78.62 for O & G at p = 0.01). Percentage increase/decrease of each parameter with respect to the previous treatment unit shows that the individual units are also performing well and their removal efficiencies are satisfactory. All the parameters studied are well within the prescribed standard for discharge of waste water to outside.